2019
DOI: 10.1038/s41598-018-38310-y
|View full text |Cite|
|
Sign up to set email alerts
|

Msx1 loss suppresses formation of the ectopic crypts developed in the Apc-deficient small intestinal epithelium

Abstract: The first step in the development of human colorectal cancer is aberrant activation of the Wnt signaling pathway. Wnt signaling hyperactivation is predominantly caused by loss-of-function mutations in the adenomatous polyposis coli (APC) gene that encodes the pathway negative regulator. In order to identify genes affected by the Apc loss, we performed expression profiling of intestinal epithelium isolated from mice harboring a conditional Apc allele. The gene encoding transcriptional factor msh homeobox 1 (Msx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 68 publications
0
26
0
Order By: Relevance
“…Whereas in colorectal cancer, compared to the adjacent normal tissues, MSX1 was shown to be down-regulated in COAD (9). However, the expression of MSX1 was also found to be significantly high in some colorectal cancer tissues (18,85).…”
Section: The Roles Of Msx Family In Different Types Of Tumorsmentioning
confidence: 97%
See 2 more Smart Citations
“…Whereas in colorectal cancer, compared to the adjacent normal tissues, MSX1 was shown to be down-regulated in COAD (9). However, the expression of MSX1 was also found to be significantly high in some colorectal cancer tissues (18,85).…”
Section: The Roles Of Msx Family In Different Types Of Tumorsmentioning
confidence: 97%
“…Transcription factors regulate each other in the regulatory network of signaling pathways, the expression of MSX can also be regulated by corresponding transcription factors in specific signaling pathways such as growth factor signals in tumors (40). In colorectal carcinoma, WNT/ β-catenin signaling activated MSX1 expression while the promoter of MSX1 was activated by β-catenin (18). Previous studies have suggested that MSX2 can also function as a downstream effector of WNT signaling in human ovarian endometrioid adenocarcinoma cells and human teratoma cells (49)(50)(51).…”
Section: Transcription Factors Several Transcription Factors Including Other Homeobox Genes Exert Different Effects On the Expression Of mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, tamoxifen-induced recombination of the Apc cKO alleles in Apc cKO/cKO Lgr5-EGFP-IRES-CreERT2 and Apc cKO/cKO Villin-CreERT2 animals allowed tissue-specific Apc inactivation in intestinal stem cells or in all intestinal epithelium cells, respectively [109,110]. In the latter strains, massive crypt hyperproliferation followed by intestinal microadenoma formation was observed already several days after tamoxifen administration (Figure 3) [111].…”
Section: Mouse Models Of Aberrant Wnt Signalingmentioning
confidence: 99%
“…The middle microphotograph shows the hyperplastic crypt compartment developed in Apc cKO/cKO Villin-CreERT2 mice seven days after tamoxifen administration; the right image shows microadenomas (red arrowheads) formed in the Apc cKO/cKO Lgr5-EGFP-IRES-CreERT2 small intestine 21 days after tamoxifen administration. Sections were counterstained with hematoxylin (blue nuclear signal); scale bar: 0.3 mm (adopted from Reference [111]).…”
Section: Figurementioning
confidence: 99%